Relative condition factor and gonado-somatic index in Sillago sihama (Forskal) - Reddy, C R; Neelakantan, B (Indian Journal of Fisheries, 2011)
The weight of a fish varies with the cube of its length. Variations from the expected weight from the length of individual fishes or group of fishes are detected by analysing the length-weight relationship. The condition factor is given by the formula K = 100 W/L 3 where’ K’ represents the condition factor. ’W’ the weight of fish and ’L’ the len rth of fish. This tormula is based on comparison with an ideal fish where the cube relationship holds good. Le Cren (1951) proposed the relative condition factor, ’Kn’, in preference to condition factor as the latter is highly influenced by many environmental and biological factors.